The Effect of Increasing Milk Production Program on Secretion Time of Colostrum in Postpartum Mothers, Sakon Nakhon Hospital - Pakdeechot, Sasithorn; Morarad, Rodjana; Sakontarat, Plengchawee (Journal of Health Science of Thailand, 2017)
The purpose of this quasi-experimental research was to compare secretion time of colostrum between mothers who had increasing milk production program and mothers who had undergone routine increasing milk production. A sample of 60 postpartum mothers who had no milk production within 2 hour postpartum, without complications, having vaginal delivery, normal breast and nipple and a new born could well suckle, without any anormalies or contraindications for breast feeding, were devided into 2 groups, 30 in a control group followed routine increasing milk production and 30 in a experimental group followed increasing milk production program. It was composed of breast massage: Self Mamma Control method (SMC), breast hot herbal compression before 24 postpartum hours, given the stimulating milk production food, good baby holding and breast feeding promotion every 2-3 hours. The program was summarized and data were collected during March 2007 - March 2008. Statistical analysis was carried out using percentage, means, standard deviation and dependent sample t-test. The results revealed that means score of secretion time of colostrum in the experimental group was lower than that of the control group. The differences between the two groups were significant (p<0.05). In conclusion, the increasing milk production program with early breast hot herbal compression, is recommended in all postpartum mothers who had no milk production.